Transcranial Doppler-Guided Deairing of a Pediatric Ventricular Assist Device: Experience with Twins. (1st January 2015) - Erdoes, Gabor; Kadner, Alexander; Hutter, Damian; Eberle, Balthasar
Abstract : We report the intraoperative courses of 2 consecutive Berlin Heart Excor® Pediatric Ventricular Assist Device implantations, in which transcranial Doppler ultrasonography helped to detect macroscopically undetected residual air bubbles captured in the pump after air removal had been correctly performed according to manufacturer's specifications. Our experience with these cases suggests that a beat-to beat deairing maneuver guided by transcranial Doppler is a useful strategy for reducing cerebral exposure to perioperative gaseous microembolism.